Rural Tourism for the Save of Agrobiodiversity and the Solution of Socio-Economic Problems of Rural - Lokutova, Olena; Onopriichuk, Diana (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
The aim of the article is to examine the theoretical foundations and practical approaches to the development of rural tourism, and also to analyze the relevance and necessity of further development of rural tourism in the context of sustainable development. First of all, we consider the terminology, concepts, necessary conditions which contribute to the development of rural tourism and sustainable tourism, its environmental aspects and the main differences from traditional tourism. The second important component of rural tourism is its significant impact on the solution of socio-economic problems of the village (self-employment and the problem of unemployment, additional income of the rural residents as well as the preservation of architectural and cultural heritage and folk traditions). Thus, considering the importance of rural tourism as a special kind of activity of rural residents (family hospitality), there is a need to further improve its legislative base, in particular, the adoption of the law of Ukraine “About rural green tourism“, the project of which was developed in 2012. Another important step for the effective development of rural tourism is to popularize it, especially in the regions of Central, Eastern and Southern Ukraine. Consulting activities (consultative support), holding conferences, seminars, training schools and other events at the level of regional and district administrations will raise the interest of the village population, and thus contribute to solving the social, economic and environmental problems of the regions. A special role in this process is played by agrarian universities (in particular, the National University of Life and Environmental science of Ukraine), institutes for improving the skills of agricultural personnel.